A canonical exegesis of the eighth Psalm : YHWH's maintenance of the created order through divine intervention - Keener, Hubert James (Journal of theological interpretation supplements ;, 2013)
Since Brevard Childs first introduced it as a "fresh approach" in the late 1960s, canonical exegesis has grown into a widely discussed and developed program--virtually a "school" of biblical interpretation--with many scholars carrying forward an approach to theological exegesis that emphasizes the role of canon as the central context for interpretation of the Christian Scriptures. In this study, Keener takes a twofold approach: (1) he demonstrates that a canonical exegesis is tenable if the task is approached with clarity regarding its core theological foundation; and (2) he applies the approach to the interpretation of the often thorny questions surrounding the understanding of Psalm 8. This is useful in that Psalm 8 touches upon several questions germane to the successful implementation of canonical exegesis due to the many intertextual connections it shares with the rest of the Bible. Keener concludes that Psalm 8 in the Old Testament represents the intersection of two trajectories: (1) the reversal motif in which YHWH maintains the created order through the exaltation of the weak and the humble; and (2) the motif of the conflicted and conflicting human, in which humans are shown as beset by trials, often failing and even occupying the role of the enemies of YHWH. A third trajectory becomes visible in the context of the New Testament, that of the redeeming Christ; this third trajectory intersects with the two Old Testament trajectories and makes possible the redemption of conflicted humanity, giving the ultimate answer to the psalmist's question, "What is the human?"